A new species of Catasetum (Cymbidieae: Catasetinae) from the Colombian Amazonia - Calderón Álvarez, R. Alexis; Bonilla Morales, Miguel M. (2023)
A new species, Catasetum caquetense from the Caquetá department of the Colombian Amazonia, is described and illustrated. Catasetum caquetense is morphologically distinct from similar species such as C. tuberculatum in itsrectangular, entire, denticulate, prominent apiculate basal callus surrounded by inconspicuous crown-shaped protrusions with an extra callus towards the apex that partially narrows towards the mid-lip. Information about its distribution, ecology, habitat, and taxonomic comments on morphologically similar species is also provided. With this addition, the genus comprises eight species in the department of Caquetá.
Se describe e ilustra una nueva especie, Catasetum caquetense del departamento del Caquetá amazonia colombiana. Catasetum caquetense difiere de especies morfológicamente similares como C. tuberculatum por el callo basal rectangular, entero, denticulado, prominentemente apiculado, rodeado de protuberancias inconspicuas en forma de corona con un callo extra hacia el ápice que se estrecha parcialmente hacia el labelo. Además, se proporciona información sobre su distribución, ecología, hábitat y comentarios taxonómicos sobre especies morfológicamente similares. Con esta adición, el género comprende ocho especies en el departamento del Caquetá.
Keywords: ORQUIDEAS -- COLOMBIA; ORQUIDEAS -- MORFOLOGIA -- COLOMBIA; PLANTAS ENDEMICAS